Comparative Study on Epidermal Moisturizing Effects and Hydration Mechanisms of Rice-Derived Glucosylceramides and Ceramides - Takeda, Shogo; Yoneda, Akari; Miyasaka, Kenchi; Manse, Yoshiaki; Morikawa, Toshio; Shimoda, Hiroshi (International Journal of Molecular Sciences, 2022)
Ceramide (Cer) plays an important role in skin barrier functions in the stratum corneum (SC). The ingestion of food-derived glucosylceramides (GlcCer) attenuates transepidermal water loss (TEWL). However, the moisturizing effects of single molecules of GlcCer and Cer remain unclear. Therefore, we herein purified 13 GlcCer and 6 Cer, including elasticamide, which has the same structure as human Cer[AP], from rice and compared their epidermal moisturizing effects in a reconstructed human epidermal keratinization model. The results obtained showed that 10 µM of 5 GlcCer[d18:2] with a 4E,8Z sphingadienine and C18 to C26 fatty acids and 10 µg/mL of 3 Cer with C23 or C24 fatty acids significantly reduced TEWL. The moisturizing effects of these GlcCer were dependent on the length of fatty acids. Furthermore, 10 µg/mL of elasticamide increased the SC Cer contents by promoting the expression of GlcCer synthase. Electron microscopic observations revealed that 1 µM of GlcCer[d18:2(4E,8Z)/26:0] increased the number of keratohyalin granules and desmosomes. Immunostaining and Western blotting indicated that 1 µM of GlcCer[d18:2(4E,8Z)/26:0] up-regulated the expression of filaggrin and corneodesmosin, which contribute to epidermal hydration. This comparative study on epidermal moisturization by GlcCer and Cer isolated from rice revealed differences in their hydration mechanisms.